Analisis Tingkat Kepuasan Pasien terhadap Pelayanan Kefarmasian di Apotek Sigma Farma Kota Bandung - Habib Shafa Thariq; Wempi Eka Rusmana (Syntax Corporation Indonesia, 2021)
Consumer goals are a person's feelings after comparing (performance or results) that are felt compared to their expectations. Service (customer service) in general is any activity aimed at providing satisfaction to customers, through this service the desires and needs of customers can be fulfilled. Pharmacies according to the Decree of the Minister of Health of the Republic of Indonesia No. 1027/MENKES/SK/IX/2004 is a place for pharmaceutical work, the provision of pharmaceutical preparations and other health supplies to the public. This study aims to determine the extent to which the level of patient satisfaction with pharmaceutical services at Apotek Sigma Farma is based on the level of service quality in physical appearance, response, certainty and empathy. This research is an observational research conducted using survey and observation method which is a descriptive study. This research was conducted at the Sigma Farma pharmacy by providing a cross sectional questionnaire to patients who visited the pharmacy. The results of the study on the level of patient satisfaction with pharmaceutical services at the Sigma Farma Pharmacy Bandung, seen from the aspect of the questionnaire above, it can be said that from a total of 8 questions from 10 people who answered, the average patient or respondent strongly agreed that the standard of pharmaceutical services at the Sigma Farma pharmacy it's been very good. No one answered disagree and strongly disagree